1991
DOI: 10.1021/bc00009a006
|View full text |Cite
|
Sign up to set email alerts
|

Astatine-211 labeling of an antimelanoma antibody and its Fab fragment using N-succinimidyl p-[211At]astatobenzoate: comparisons in vivo with the p-[125I]iodobenzoyl conjugate

Abstract: Astatine-211 labeling of an antimelanoma antibody, NR-ML-05, and its Fab fragment with N-succinimidyl p-[211At]astatobenzoate (2a) has been described. Preparation of the astatinated intermediate 2a was accomplished by distilling astatine-211 from an irradiated bismuth target directly into a reaction mixture containing an organometallic compound, N-succinimidyl p-(tri-n-butylstannyl)benzoate (1), and an oxidant, N-chlorosuccinimide, in 5% HOAc/MeOH. Trapping of distilled astatine as 2a was found to be efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 33 publications
2
46
0
Order By: Relevance
“…This elevated uptake points to a probable in vivo deastatination of the antibody conjugate, since free astatine is known to accumulate in the thyroid and stomach (35). Other studies using different antibodies revealed the same effect, which means it is not trastuzumab-related (26). Treatment with perchlorate could alleviate this problem (35), but if this was impossible, loss of thyroid function can be alleviated by modern medicine to a large extent and could be deemed as an acceptable side effect of tumour treatment in some cases.…”
Section: Days -------------------------------------------------------mentioning
confidence: 84%
See 1 more Smart Citation
“…This elevated uptake points to a probable in vivo deastatination of the antibody conjugate, since free astatine is known to accumulate in the thyroid and stomach (35). Other studies using different antibodies revealed the same effect, which means it is not trastuzumab-related (26). Treatment with perchlorate could alleviate this problem (35), but if this was impossible, loss of thyroid function can be alleviated by modern medicine to a large extent and could be deemed as an acceptable side effect of tumour treatment in some cases.…”
Section: Days -------------------------------------------------------mentioning
confidence: 84%
“…radiolysis. Indirect astatination of antibodies using succinimidyl ester of para-astatobenzoate is a wellestablished procedure, which usually produces a labelled antibody with preserved immunoreactivity (26,27). Such labelling modifies lysine residues, and its safety should be demonstrated for each antibody.…”
Section: Days -------------------------------------------------------mentioning
confidence: 99%
“…In most cases, the biodistribution of a protein radiolabeled with 125 I and 211 At are quite similar (11,15,16), but there have been previous reported exceptions (17,18), especially when smaller molecules, such as antibody fragments have been used. The results from these studies, with high uptake in stomach, lungs and spleen, indicate that free 211 At is released in vivo.…”
Section: Discussionmentioning
confidence: 97%
“…D-particles have been discussed as candidates for radiation therapy because of their high linear energy transfer (LET) 1,2,3 . With its halogen-like chemistry, 211 At, which emits D-particles, has the possibility of being used in a number of compounds.…”
Section: Introductionmentioning
confidence: 99%